Analisis Perbandingan Sifat Mekanik dari Variasi Kandungan Filler Serbuk Cangkang Kerang Darah dan Serbuk Cangkang Telur dengan Pengikat Karet Alam - Hisyam, Hafiz Hade; Listijorini, Erny; Dwinanto, Dwinanto (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2024)
Technological advancements drive innovation in environmentally friendly material science. Environmental issues, such as pollution from toxic substances, motivate research into sustainable biocomposites. One of the widely studied biocomposites is a natural rubber-based composite with fillers that enhance its mechanical properties. Calcium carbonate (CaCO3) is a popular inorganic filler. Marine shell waste, especially cockle shells (Anadara granosa) and eggshells, pose serious environmental problems. Cockle shells contain 95.7% calcium carbonate. Eggshells also have the potential to improve the mechanical properties of elastomer composites. This study aims to compare the effects of cockle shell and eggshell fillers on the mechanical properties of natural rubber through tensile testing, to determine the more effective filler in improving the mechanical performance of the composite. Test results show that cockle shells have a higher ultimate tensile strength (UTS) (up to 20.3 MPa) and a higher Young's modulus (up to 3.4 GPa) compared to eggshells, which have the lowest UTS of 17.94 MPa and the lowest Young's modulus of 1.8 GPa. This indicates that cockle shells are stiffer. However, eggshells have a higher yield strength (up to 15.2 MPa), indicating better elasticity. Overall, cockle shells enhance strength and stiffness, while eggshells excel in elasticity